Notch Signaling Modulates Macrophage Polarization and Phagocytosis Through Direct Suppression of Signal Regulatory Protein α Expression - Lin, Yan; Zhao, Jun-Long; Zheng, Qi-Jun; Jiang, Xun; Tian, Jiao; Liang, Shi-Qian; Guo, Hong-Wei; Qin, Hong-Yan; Liang, Ying-Min; Han, Hua (Frontiers in Immunology, 2018)
The Notch pathway plays critical roles in the development and functional modulation of myeloid cells. Previous studies have demonstrated that Notch activation promotes M1 polarization and phagocytosis of macrophages; however, the downstream molecular mechanisms mediating Notch signal remain elusive. In an attempt to identify Notch downstream targets in bone marrow-derived macrophages (BMDMs) using mass spectrometry, the signal regulatory protein α (SIRPα) appeared to respond to knockout of RBP-J (recombination signal-binding protein Jk), the critical transcription factor of Notch pathway, in macrophages. In this study, we validated that Notch activation could repress SIRPα expression likely via the Hes family co-repressors. SIRPα promoted macrophage M2 polarization, which was dependent on the interaction with CD47 and mediated by intracellular signaling through SHP-1. We provided evidence that Notch signal regulated macrophage polarization at least partially through SIRPα. Interestingly, Notch signal regulated macrophage phagocytosis of tumor cells through SIRPα but in a SHP-1 independent way. To access the translational value of our findings, we expressed the extracellular domains of the mouse SIRPα (mSIRPαext) to block the interaction between CD47 and SIRPα. We demonstrated that the soluble mSIRPαext polypeptides could promote M1 polarization and increase phagocytosis of tumor cells by macrophages. Taken together, our results provided new insights into the molecular mechanisms of Notch-mediated macrophage polarization and further validated SIRPα as a target for tumor therapy through modulating macrophage polarization and phagocytosis.